Combination of Surface Charge and Size Controls the Cellular Uptake of Functionalized Graphene Sheets. (10th July 2017) - Tu, Zhaoxu; Achazi, Katharina; Schulz, Andrea; Mülhaupt, Rolf; Thierbach, Steffen; Rühl, Eckart; Adeli, Mohsen; Haag, Rainer
Abstract : A fundamental issue for biomedical applications of graphene is the correlation between its physicochemical properties and cellular uptake mechanism. However, such studies are challenging due to the intrinsic polydispersity of graphene. In this work, a series of water soluble graphene sheets with the same polymer coverage, density of functional groups, and fluorescence intensity but three different sizes and surface charges are produced. The effect of the latter two factors and their combination on the mechanism of cellular uptake and intracellular pathways of these defined nanosheets is investigated via confocal and Raman microscopies. While positively (NH3 + ) and negatively (OSO3 − ) charged sheets show an energy dependent uptake, their neutral analogs do not show any significant uptake. The cellular uptake efficacy of positively charged graphene sheets is independent of the size and occurs both through phagocytosis and clathrin‐mediated endocytosis pathways. However, cellular uptake efficacy of graphene sheets with negative surface charge strongly depends on the size of the sheets. They cross the membrane mainly through phagocytosis and sulfate‐receptor‐mediated endocytosis. This study demonstrates that the impact of the size of graphene derivatives on their cellular uptake pathways highly depends on their surface charges and vice versa. Abstract : A family of graphene derivatives with defined polymer coverage, density of functional groups, fluorescence intensity, surface charge, and size are synthesized and their cellular uptake is investigated. It is found that the combination of size and surface charge plays a pivotal role in the cellular uptake pathways of these graphene derivatives.